KARAKTERISASI SIFAT FISIKA KARBON AKTIF TEMPURUNG KELAPA DENGAN VARIASI KONSENTRASI AKTIVATOR SEBAGAI KONTROL KELEMBABAN - Taer, E.; Oktaviani, T.; Taslim, R.; Farma, R. (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Has successfully carried out a study of the effect of different concentrations of KOH activator in coconut shell charcoal as a humidity control. KOH concentration on the activation process of coconut shell charcoal varied as much as 1 M, 2 M and 3 M. The activation process is done for two hours at room temperature. The activated carbon is washed using distilled water until the pH of the washing water became neutral and then followed by drying for 24 hours at a temperature of 100ËšC. Physical properties was studiod suchasi, surface morphology, element content and degree of cristalinity using a Scanning Electron Microscope, Energy Dispersive X-Ray and X-Ray Diffraction instrumen. Coconut shell activated carbon used as the coating material for tosting chamber. The study of humidity charavationtic with time priode of 15 minutes for 2 hours. Humidity value at the end of 2 hours of testing for concentration of carbon with 1, 2 and 3 M KOH is 89%, 88% and 85% respectively. This study shows the activation of KOH concentration depending on coconut shell carbon effect on humidity test chamber. Keywords: coconut shell, potassium hydroxide, Humidity.